Somatic Embryogenesis of Melon (Cucumis melo L.) As Affected by Culture Media and Composition of Plant Growth Regulators - Furqoni, Hafith; Efendi, Darda (Journal of Tropical Crop Science, 2018)
Conventional production of melon hybrid seeds requires a long time. Propagation through plant tissue culture can be an alternative method to produce hybrid melon seedlings in order to fulfill the high demand for uniform seedlings. Our current study was aimed to determine the type of propagation media and the best concentration of picloram for the induction of somatic embryogenesis in melon from young seed explants. The study was expanded to examine the effective concentrations of two of auxins, 2-4 D and NAA, combined with BAP to induce somatic embryogenesis in melon using hypocotyl explants. The experiment was conducted at Plant Tissue Culture Laboratory, Department of Agronomy and Horticulture, Faculty of Agriculture, Bogor Agricultural University. The experiment was arranged in a randomized complete block design with three replications. The first experiment tested three types of planting media (MS, B5, and WPM) and four levels of picloram concentration (0, 0.5, 1.0, 1.5 mg.L-1). The second experiment tested auxin (2,4-D and NAA) concentrations of 0, 1, 2, 3, 4, 5 mg.L-1 and two BAP concentrations, 0 and 1 mg.L-1. The first study showed that no somatic embryos were formed with the media types and picloram concentration tested; the seeds, however, germinated and formed callus. In the second study, there was an interaction between concentration levels of auxin (2,4-D and NAA) and BAP on induction of somatic embryos using hypocotyl explants. Somatic embryo formation can be induced with treatment of 1 mg.L-1 NAA + 0.1 mg.L-1 BAP and 2 mg.L-1 NAA + 0.1 mg.L-1 BAP. The highest yield of embryos formation was with the treatment of 1 mg.L-1 NAA + 0.1 mg.L-1 BAP at 0.53 embryos per explant. Keywords: embryogenesis, tissue culture media, melon, Picloram, 2,4 D, BAP